Transformation of the spectrum of coupled nonlinear oscillators during transition to the chaotic dynamic - Syaber, S.S.; Anisimov, I.O. (Вопросы атомной науки и техники, 2014)
Transition to the chaotic dynamic in the system of two coupled conservative nonlinear oscillators has been studied. Oscillators are represented by conservative LC circuits with nonlinear capacitors. The system exhibits chaotic behavior in some range of initial conditions. We focus on the spectra analysis of the oscillations that correspond to qualitatively different phase trajectories. Certain correspondence with the signal modulation has been found. Исследуется переход к хаотической динамике в системе двух связанных консервативных нелинейных осцилляторов. Осцилляторы являются колебательными контурами с нелинейными конденсаторами. Для некоторых начальных условий в системе наблюдается хаотическая динамика. Основное внимание уделяется анализу спектров, отвечающих качественно отличающимся фазовым траекториям. Обнаружена некоторая схожесть с процессами модуляции сигналов. Досліджується перехід до хаотичної динаміки в системі двох зв’язаних консервативних осциляторів. Осцилятори є коливальними контурами з нелінійними конденсаторами. Для деяких початкових умов у системі спостерігається хаотична динаміка. Основна увага приділяється аналізу спектрів, що відповідають якісно відмінним фазовим траєкторіям. Знайдена певна схожість із процесами модуляції сигналів.